Convergent geographic patterns between grizzly bear population genetic structure and Indigenous language groups in coastal British Columbia, Canada - Lauren H. Henson (Resilience Alliance, 2021)
Landscape genetic analyses of wildlife populations can exclude variation in a broad suite of potential spatiotemporal correlates, including consideration of how such variation might have similarly influenced people over time. Grizzly bear (Ursus arctos) populations in what is now known as coastal British Columbia, Canada, provide an opportunity to examine the possible effects of a complex set of landscape and human influences on genetic structure. In this collaboration among the Nuxalk, HaíÉ«zaqv, Kitasoo/Xai'xais, Gitga'at, and Wuikinuxv First Nations and conservation scientists, we characterized patterns of genetic differentiation in the grizzly bear, a species of high cultural value, by genotyping 22 microsatellite loci from noninvasively collected hair samples over a 23,500 km² area. We identified three well-differentiated groups. Resistance surfaces, which incorporated past and present human use, settlement, and landscape resistant features, could not explain this pattern of genetic variation. Notably, however, we detected spatial alignment between Indigenous language families and grizzly bear genetic groups. Grizzly bears sampled within an area represented by a given language family were significantly similar to those sampled within that language family (P = 0.001) and significantly divergent to those sampled outside the language family (P = 0.001). This spatial co-occurrence suggests that grizzly bear and human groups have been shaped by the landscape in similar ways, creating a convergence of grizzly bear genetic and human linguistic diversity. Additionally, grizzly bear management units designated by the provincial government currently divide an otherwise continuous group and exclude recently colonized island populations that are genetically continuous with adjacent mainland groups. This work provides not only insight into how ecological and geographic conditions can similarly shape the distribution of people and wildlife but also new genetic evidence to support renewed, locally led management of grizzly bears into the future.